Post-treatment with a Hydrogen Sulfide Donor Limits Neuronal Injury and Modulates Potassium Voltage-gated Channel Subfamily D Member 2 (Kv4.2) and Potassium Channel Interacting Protein 3 (KChIP3) During Transient Global Cerebral Ischemia - Ping Bai, Cheng; Zhao, ChenLiang; Shen, Lijuan (Current Neurovascular Research, 2017)
Background: Although the neuroprotective effect of sodium hydrosulfide (NaHS, a hydrogen sulfide donor) pretreatment has been revealed, the effect of NaHS post-conditioning remains largely unknown. Objective: We aimed to investigate the neuroprotective effect of NaHS post-conditioning against transient Global Cerebral Ischemia (tGCI)-induced hippocampal CA1 injury and its underlying molecular mechanism. Methods: A tGCI rat model was established using the four-vessel occlusion method for 15 min of ischemia. The survival of hippocampal neurons was determined by Nissl staining and NeuN immunostaining. Protein expression of potassium voltage-gated channel subfamily D member 2 (Kv4.2) and potassium channel interacting protein 3 (KChIP3) was assessed by Immunohistochemistry (IHC) and Western blot. Results: Decreased concentrations (12 and 24 μmol/kg) of NaHS post-conditioning significantly increased the numbers of survival neurons and NeuN-positive neurons in the hippocampal CA1 region at 7 days post-tGCI (all P&<0.05). NaHS post-conditioning (24 μmol/kg) at 12 and 24 hr posttGCI can achieve the best protective effect (both P&<0.05). IHC data demonstrated that NaHS postconditioning (24 μmol/kg) markedly attenuated tGCI-induced down-regulation of Kv4.2 protein in the hippocampal CA1 region at 26 hr post-tGCI. Confocal images showed that Kv4.2 did not express in the neuronal nuclei but predominantly express in the neuronal dendrites. In addition, NaHS post-conditioning significantly up-regulated Kv4.2 and down-regulated KChIP3 in tGCI rats at 26 and 168 hr post- tGCI (all P&<0.05). Conclusion: Decreased concentrations of NaHS post-conditioning at 12-24 hr post-tGCI effectively protected hippocampal CA1 neurons from tGCI-induced injury, which may be through regulating the expression of Kv4.2 and KChIP3.
Keywords: neuroprotection